2021
DOI: 10.1001/jamanetworkopen.2021.4846
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Atezolizumab Plus Bevacizumab vs Sorafenib for Patients With Unresectable or Metastatic Hepatocellular Carcinoma

Abstract: IMPORTANCE Atezolizumab plus bevacizumab as a first-line therapy for patients with unresectable or metastatic hepatocellular carcinoma has been shown to improve overall and progression-free survival compared with standard sorafenib treatment. However, because of the high cost of atezolizumab plus bevacizumab, assessment of its value by considering both efficacy and cost is needed.OBJECTIVE To evaluate the cost-effectiveness of atezolizumab plus bevacizumab vs sorafenib for patients with unresectable or metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 54 publications
(161 reference statements)
0
48
0
1
Order By: Relevance
“…Some studies have evaluated the cost-effectiveness of immunotherapy in HCC. Almost all studies have shown that immunotherapy is unlikely to be a cost-effective option compared to sorafenib, although the ICERs reported by these studies vary ( Hou and Wu 2020 ; Chiang et al, 2021a ; Su et al, 2021 ; Wen et al, 2021 ; Zhang et al, 2021 ). Four of these studies that used clinical data from the IMbrave150 trial evaluated the economics of atezolizumab plus bevacizumab in the first-line treatment of HCC from the perspective of the United States ( Chiang et al, 2021a ; Su et al, 2021 ; Wen et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated the cost-effectiveness of immunotherapy in HCC. Almost all studies have shown that immunotherapy is unlikely to be a cost-effective option compared to sorafenib, although the ICERs reported by these studies vary ( Hou and Wu 2020 ; Chiang et al, 2021a ; Su et al, 2021 ; Wen et al, 2021 ; Zhang et al, 2021 ). Four of these studies that used clinical data from the IMbrave150 trial evaluated the economics of atezolizumab plus bevacizumab in the first-line treatment of HCC from the perspective of the United States ( Chiang et al, 2021a ; Su et al, 2021 ; Wen et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the partitioned survival model can use the survival functions fitted to the original survival data directly and is more likely to deliver real health outcomes and associated costs. Therefore, it has distinct advantages over the Markov model ( Connock et al, 2019 ) and is being increasingly used to track disease progression in the field of oncology in recent years ( Wan et al, 2017 ; Connock et al, 2019 ; Su et al, 2021 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This corresponded to „70,581 ($10,054) and „2,11,743 ($30,162) in 2019, respectively ( National Bureau of Statis, 2019 ). The WTP threshold in the US was between $1,00,000 and $1,50,000 per QALY gained ( Messali et al, 2013 ; Su et al, 2021 ; Zhang et al, 2021 ). All these parameters were entered into a model in which the utilities were assigned the beta distribution and costs were assigned the gamma distribution.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of cost-effectiveness the combination of atezolizumab and bevacizumab was shown to be of clinical benefit but was not cost-effective compared to sorafenib. The incremental increase in the quality-of-life years per patient was US$ 156,210 and an increment cost effective ratio of 322,500 per quality-adjusted life year (10).…”
Section: Editorialmentioning
confidence: 98%